Evaluation of Aging Structures for Silver Carp from Midwestern U.S. Rivers. (6th August 2013) - Seibert, Justin R.; Phelps, Quinton E.
Abstract: To combat the potential deleterious effects that Silver Carp Hypophthalmichthys molitrix have on native populations, management of this species is essential. Before developing population‐level models, a determination of which aging structure for estimating the age of Silver Carp is needed. To our knowledge, no consensus has been reached on which structure should be used for estimating Silver Carp ages. We collected 120 Silver Carp from the Illinois, Mississippi, Missouri, and Ohio rivers via electrofishing to evaluate aging structures. Removal time, processing time, and discernible annuli were evaluated for scales, opercles, vertebrae, pectoral fin rays, postcleithra, and asterisci and lapilli otoliths. Asteriscus otolith, opercle and scale annuli were difficult to discern and not evaluated further. Total processing times for postcleithra (246.1 s) and lapilli (251.2 s) were the most time‐efficient; pectoral fin rays and vertebrae were more time intensive. Between‐reader precision and agreement rates resulted in lapilli being the most precise, followed by postcleithra, pectoral fin rays, and vertebrae. Comparisons of structures with lapilli revealed that pectoral fin rays exhibited 78% agreement, 49% agreement with postcleithra, and 53% agreement for vertebrae. In terms of agreement ±1 year to lapilli, pectoral fin ray, postcleithrum, and vertebra resulted in high agreement (>85%). Age bias plots revealed that these discrepancies consistently underestimated ages compared with lapilli. Discrepancies may be attributed to erosion of the central lumen of fin rays and postcleithra, while locating the first annulus on vertebrae may have led to this disparity. Based on previous studies, evaluation of overall processing times, assessment of between‐reader precision, between‐reader agreement rates, and bias that may be involved with alternative structures, we recommend lapilli otoliths be used for estimating age of Silver Carp. Future efforts should focus on validating accuracy of lapilli for estimating Silver Carp ages. Received March 1, 2013; accepted June 5, 2013